A Decline in Labor's Share with Capital Accumulation and Complementary Factor Inputs: An Application of the Morishima Elasticity of Substitution - Saumik Paul (Institute of Labor Economics (IZA), 2019)
The role of capital accumulation as a driver of the labor income share requires capital and labor to be substitutes, which appears paradoxical in a world predominantly characterized by complementarity between capital and labor. This paper argues that the composition of skills in the labor force and an identification of the elasticity parameters between capital and different skills of labor can reconcile the opposing views. Using a framework with capital-skill complementarity and variable substitution elasticities, the Morishima elasticity of substitution is applied to identify the elasticity parameters at different skill levels and derive the necessary condition for capital accumulation to coexist with a declining labor income share when capital and labor are complements. Empirical evidence supports this proposition.
Keywords: E21; E22; E25; 330; labor income share; production function; Morishima elasticity of substitution